2019
DOI: 10.3390/membranes9020024
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on the Resistance-in-Series Model in Membrane Bioreactors (MBRs)

Abstract: The cake layer deposited on the membrane modules of membrane bioreactors (MBRs), especially under a submerged configuration, represents a relevant and fundamental mechanism deeply influencing the development of membrane fouling. It negatively affects the total resistance to filtration, while exerting a positive effect as a “pre-filter” promoting the “dynamic membrane” that protects the physical membrane from internal fouling. These two opposite phenomena should be properly managed, where the submerged membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 184 publications
(322 reference statements)
2
30
0
Order By: Relevance
“…Pilot plant operation and data capture was fully automated. Calculation of permeate flux and recovery was according to Equations (1) and (2). Operation of the UF pilot plant was quasi-continuous-a centrate batch was continuously processed during working hours and operation was stopped during nights and weekends.…”
Section: Centrate To Ultrafiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot plant operation and data capture was fully automated. Calculation of permeate flux and recovery was according to Equations (1) and (2). Operation of the UF pilot plant was quasi-continuous-a centrate batch was continuously processed during working hours and operation was stopped during nights and weekends.…”
Section: Centrate To Ultrafiltrationmentioning
confidence: 99%
“…Ultrafiltration (UF) is a state-of-the-art technology for municipal and industrial wastewater treatment, e.g., as membrane bioreactor in combination with activated sludge processes [1]. The interaction mechanisms between biological suspension and membrane surface are well understood and commonly classified into deposition, reversible and irreversible (bio-)fouling, and pore-blocking [1,2]. Solid concentration, particle size and structure as well as sludge rheology have an impact on membrane fouling [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The average flux decline rate (FD, %) for CUFM and HFUFM was 37.08% ± 4.54% and 37.56% ± 5.28%, respectively, showing that there were no significant differences ( p > 0.05), which indicated that the fouling characteristics of CUFM and HFUFM were similar in the batch process. The decline of the membrane flux was due to the forming of the cake layer on the membrane surface, which caused membrane fouling and resulted in a decrease of the membrane permeability [ 37 ]. The results were similar to the data from other studies presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the membrane service-life preservation, it is of paramount importance to minimize the pore-blocking mechanism or, alternatively, maximize the recovery of the membrane permeability with chemical cleaning operations. The highest value of the "irremovable fouling", defined as the residual portion of fouling after chemical cleanings (Di Bella and Di Trapani, 2019), was observed in Period 4, whereas the lowest in Period 1. This result indicated that the integration of the AMSR might cause a potential decrease in the membrane service-life.…”
Section: Membrane Fouling Analysismentioning
confidence: 99%